(untitled) (Berlin, 2017)
This volume consists of papers selected from contributions to the 2013 conference of the European Society for Translation Studies (EST 2013) and the 2015 edition of the Translation in Transition conference (TiT 2015), both held at the Faculty for Translation Studies, Linguistics and Cultural Studies of the University of Mainz in Germersheim, Germany. It addresses the above-mentioned issues from several perspectives: multi-method product- as well as process-based research gives insights into translation as well as interpreting phenomena
Keywords: Biên dịch và phiên dịch.,Translating and interpreting